Parenting interventions for people with schizophrenia or related serious mental illness - Radley, J; Grant, C; Barlow, J; Johns, L (Cochrane Collaboration, 2020)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows:. To assess the effects of parenting interventions for people with schizophrenia or related serious mental illness.